Management of Postoperative Myocardial Injury After Non-cardiac Surgery in Patients Aged ≥ 80 Years: Our 10 Years' Experience - Gao, Linggen; Chen, Lei; Wang, Bin; He, Jing; Liu, Chaoyang; Wang, Rong; Cheng, Rui (Frontiers in Cardiovascular Medicine, 2022)
Background: Postoperative myocardial injury (PMI) is associated with short- and long-term mortality. The incidence of PMI in the very old patients is currently unknown. There is currently neither known effective prophylaxis nor uniform strategy for the elderly with PMI. Objective: To share our 10 years’ experience in comprehensive management of PMI after noncardiac surgery in patients aged ≥ 80 years. Methods: In this case series, we retrospectively collected and assessed the 2984 cases aged ≥ 80 years who accepted noncardiac surgery from 2011 to 2021 at the second Medical Center, Chinese PLA General Hospital. The incidence, risk factors, management strategy and prognosis of surgical patients with PMI was analyzed. Results: A total of 2984 patients met our inclusion criteria. The overall incidence of PMI was 14.0%. In multivariable analysis, coronary artery disease, chronic heart failure, hypotension was independently associated with the development of PMI. Patients with PMI were at higher risk of death (OR, 2.69; 95% CI, 1.78-3.65). They were more likely to have received low molecular heparin, anti-plantlet therapy, beta-blocker, early coronary angiography and statin than patients without PMI. The 30-day (0.96% vs 0.35%; OR 3.46; 95% CI, 1.49–7.98;P < 0.001) and 1-year mortality (5.37% vs 2.60%; OR 2.35; 95% CI, 1.12–6.53; P < 0.001) was significantly higher in patients with PMI compared with those without PMI. Conclusions: The incidence of PMI in the very old patients was high. PMI is associated with an increased risk of 30 days and 1-year morality. These patients can benefit from intensification of assessment and individualizing care of multi-morbidities during perioperative period. Especially cardiovascular medical treatments, such as antiplatelets, anticoagulation, β-blockers and statins are very important for patients with PMI.